Nitrogen assimilation by nodulate plants of Phaseolus vulgaris L. and Vigna unguiculata (L.) Walp - Neves, Maria C.P.; Fernandes, Manlio S.; Sá, Marcia F.M. (Pesquisa Agropecuaria Brasileira, 2014)
Under field conditions, the processes of nitrogen assimilation via nitrogenase and nitrate-reductase, the transport and the accumulation of nitrogen in nodulated plants of Phaseolus vulgaris cv. Rio Tibagi and Vigna unguiculata cv. Vita 34 were compared and contrasted. V. unguiculata showed better nodulation than P. vulgaris and consequently had higher rates of nitrogenase activity. The small nodulation of P. vulgaris resulted in greater dependence on soil mineral nitrogen as indicated by the higher rates of nitrate-reductase activity compared with V. unguiculata, especially during reproductive stage of growth. The superiority of V. unguiculata in terms of assimilation and remobilization of stored nitrogen resulted in a seed yield 28% greater than that of P. vulgaris. There was no correlation between the seasonal changes in the ureides content of the xylem sap and the nitrogenase activity for both plant species. However. P. vulgaris showed a negative correlation between the nitrate-reductase activity and the ureide content of the sap indicating that the metabolic pathways leading to ureide production operates alternatively to nitrate assimilations.